Liquid Metal Enabled Thermoelectric Effects: Fundamental and Application - Guan, Tangzhen; Gao, Jianye; Hua, Chen; Tao, Yiyue; Ma, Yibing; Liu, Jing (Advanced functional materials, 2025)
The thermoelectric (TE) effect, capable of directly converting heat into electrical energy, has catalyzed the development of numerous next‐generation functional devices. However, traditional TE generators (TEGs), predominantly composed of rigid materials, are unable to maintain synchronous deformation under bending, twisting, or stretching, thereby limiting their application potential. Liquid metal (LM), with its exceptional electrical conductivity, flexibility, thermal conductivity, self‐healing properties, and unique TE effects, presents a compelling alternative as a conductive and heat‐transfer material. By integrating LM with TE effects, TEGs can achieve flexibility, stretchability, and self‐healing capabilities, enhance the thermal conductivity of encapsulating materials (ECMs), reduce interfacial contact resistance, and improve overall performance. This article provides a comprehensive review of the cutting‐edge intersection between LM and TE effects, encompassing applications of LM in interconnects (INCs), heat‐conductive materials, and the fabrication of TE legs. Subsequently, the unique TE effects at liquid–liquid interfaces between gallium and commonly used LMs are reviewed. Additionally, the emerging process of fabricating thermoelectric materials (TEMs) using LM‐printed semiconductors is explored. Finally, based on an evaluation of the latest advancements in this field, the challenges and promising directions for future research at the intersection of LM and TE effects are discussed. This review systematically explores liquid metal (LM)‐enabled thermoelectric (TE) effects, highlighting fundamental properties and multifunctional application scenarios. With unique traits such as fluidity, high electrical/thermal conductivity, and self‐healing, LMs impart stretchability and self‐repair capabilities to TE devices. Key challenges and future research opportunities for advancing this emerging field are also discussed.